Metamorphism and tectonics: the role in structurally-compositional transformation of chrompshinelides from ultramafites - Alexey Nikolaevich Yurichev (Известия Томского политехнического университета: Инжиниринг георесурсов, 2017)
The relevance of the work is caused by the need to identify new local evaluation criteria of potential chromite mineralization, being currently scarce raw material for Russia, in ultramafic massifs of ophiolite complexes. The main aim of the paper is to assess the nature of the effect of regressive metamorphism and post-ore tectonics on morphological safety of chromite ore body and its material composition for further predicting the quality of expected mineralization. The methods used in the work: study of silicate and ore minerals in transparent sections and polished sections on the polarizing microscope AxioScope Carl Zeiss; evaluation of chemical composition of chromosphinelides on scanning electron microscope Tescan Vega II LMU, equipped with energy-dispersive spectrometer (detector Si (Li) Standard) INCA Energy 350 and wave-dispersive spectrometer INCA Wave 700. The results. Criteria of preservation of chromite mineralization and its qualitative composition are determined by the nature of post-ore processes of metasomatism and tectonics. Forecasting the quality of expected chromite mineralization is possible only at simultaneous evaluation of these two converting agents. Metasomatism of ore chromospinelides is caused by kinetic factor, which is manifested in decrease of intensity of metamorphogenic processes with increase in density of dissemination of chromite mineralization and in size of ore bodies. Densely embedded and massive ores, which integrity is not disturbed by tectonic action, almost completely retain their qualitative composition and industrial properties at any degree of metasomatic manifestation. Otherwise, the boudinage of ore bodies occurs, small scattered lenses are formed, individual grains are splitted and crushed and, as consequence, the intensity of their metamorphogenic transformation (removal of Al, Mg and Cr and accumulation of Mn and Fe3+) increases, up to the total loss of their industrial value.